Hubungan Pengetahuan Ibu Dan Sumber Informasi Dengan Pemberian Imunisasi Measles Rubella - Yunola, Satra; Sari, Erma Puspita (JOURNAL OF MIDWIFERY SCIENCE, 2025)
Based on data published by the World Health Organization (WHO) in 2015, Indonesia is one of the 10 countries with the largest number of measles cases in the world. To find out the relationship between knowledge, sources of information and the provision ofMeasles Rubella immunization. This is design is quantitative by using an analytical survey method where this study uses a cross sectional approach. The population or subjects in this study were mothers who had babies from 9 months to 6 years old who were in the puskesmas, totaling 70 respondents. The sampling technique used Accidental Sampling. Data analysis using bivariate analysisand univariate analysis. The results showed that there was a relationship between mother's knowledge and sources of information with the provision of measles rubella immunization. Knowledge variable obtained value = 0.006. Thus the hypothesis that there is a significant relationship between mother's knowledge and the provision of measles rubella immunization. Variable source of information obtained value = 0.138. Thus the hypothesis that there is a significant relationship between the source of information and the provision of measles rubella immunization is not statistically proven. There is a relationship between mother's knowledge and information sources with the provision of measles rubella immunization.